Comparative studies of terahertz-based optical properties in transmission/reflection modes of GaSe: S and measurement of its scattering losses due to surface roughness for efficient terahertz generation - Ghorui, Chandan; Kidavu, Arjun V.; Kumar, Naveen P.; Das, S.; Chaudhary, A. K.; Andreev, Yury M. 1946- (Physica scripta)
The paper reports the efficient terahertz generation using nonlinear optical rectification process and comparative studies of optical, dielectric, and surface scattering properties of 1.0 mm thin GaSe: S crystal in transmission/reflection modes. We employed 800 nm wavelength of 140 fs and 50 fs pulse durations obtained from Ti: Sapphire oscillator and amplifier systems at 80 MHz and 1 kHz repetition rates, respectively, and evaluated the THz generation potential and optical properties such as refractive index, absorption coefficients, relative permittivity in transmission mode. In the next step, the crystal was subjected to a commercial THz system of 0.3 picosecond pulses at 100 MHz repetition rate in reflection geometry and once again recorded the similar parameters and compared with the transmission mode data. In addition, these data were used to measure the scattering losses from the surface of the crystal in terms of surface roughness, optical impedance, and Fresnel's reflection coefficients. The maximum generated THz power was of the order of 4.5 μW with conversion efficiency (η) ∼ 2.2 × 10−3%. The measured THz efficiency was found equivalent to 20 mm thick GaSe crystal used in the difference frequency mixing technique. Finally, we have measured the Rayleigh roughness factor (g) of the crystal surface at different THz frequencies. When g < 1 (for small roughness) the Fresnel reflection loss factor becomes 0.75 at 1.4 THz frequency range which helps to enhance the generated signal.